Double-Exponential-X Family of Distributions: Properties and Applications - Bashiru, Kehinde Adekunle; Ojurongbe, Taiwo Adetola; Sola, Lawal; Adeboye, Nureni .Olawale; Afolabi, Habeeb Abiodun (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
A new family of distribution named Double-Exponential-X family is proposed. The proposed family is generated from the double exponential distribution. The forms of the probability densities and hazard functions of two distinct subfamilies of the proposed family are examined and reported. Generalproperties such as moment, survival, order statistics, probability weighted moments and quartile functions of the models are investigated. A sub family of the developed family of double –Exponential-X family of the distribution known as double-Exponential-Pareto distribution was used to fit a real life data on the use of antiretroviral drugs. Molecular simulation of efficacy of antiretroviral drugs is conducted to evaluate the performance of the model. The models were tested using some models diagnostic tests and it was revealed that the proposed model was better than the ones proposed before it from the same family and also, stochastic dominance method was used to affirm the best antiretroviral drugs used in the study.